Analysis of Diastolic Left Ventricular Function in Adolescents with Juvenile Systemic Lupus Erythematosus - Loureiro,Talita Nolasco (2021)
Abstract Background Juvenile systemic lupus erythematosus (JSLE) is a chronic inflammatory disease that affects the heart in 50% of cases. The behavior of diastolic function in adolescents and the predictors of its occurrence by conventional echocardiography are poorly established. Objectives This study aimed to evaluate diastolic function in adolescents with JSLE and to identify possible predictors of its occurrence by conventional echocardiography. Methods Cross-sectional, observational, control group study in a tertiary hospital of 49 adolescents with JSLE and 49 controls, using the EACVI 2016 guideline classification. Statistical methods used were Fisher and Mann-Whitney tests. Multivariate logistic regression models were constructed. A significance level of 5% was adopted. Results Among 98 patients, the JSLE group had higher indexed left atrial volume (p <0.001), lower lateral E' value (p<0.001) and lower E/A ratio value (p<0.001). The diagnosis of JSLE was associated with a higher chance of increased left atrial index volume (OR 3.3; p value 0.03). Conclusions Based on the 2016 guideline, no diastolic dysfunction was found in JSLE. However, differences in the analyzed echocardiographic parameters were found in these adolescents.